Pcms in buildings: compatibility with container materials and analysis of environmental impacts (2019)
Contemporary architecture emphasizes energy efficiency and utilization of renewable energy sources. Main issues connected with these sources are instability of the energy supply and temporal mismatch between energy demand and supply. The solution for both these issues is suitable energy storage technology. This creates opportunity for utilization of latent heat storage (LHS) in phase change materials (PCMs). LHS technologies are already in use for example in solar thermal collectors. However their wider application is limited by lack of credible information on the properties of PCMs and their interactions with other materials. The aim of this paper is to reduce the lack of knowledge in this field. It presents results of long-term experiment evaluating the compatibility of selected organic and inorganic PCMs and metals (possible container materials). This experiment tried to find suitable material pairs that would ensure flawless functionality of the LHS system without corrosion, leakage or other defects. The experiment was followed by evaluation of the environmental impacts of hypothetical application of the tested materials. The results of this environmental assessment were also compared with a reference case representing traditional heat storage options to provide further insight regarding suitability of real-life applications of the tested materials. The results indicate that stainless steel is the most stable of the tested metals, which makes it most suitable PCM containers. However the environmental assessment suggests otherwise. Environmental impacts of the evaluated steel-PCM combinations are the highest. In fact all evaluated metal-PCM combinations have higher environmental impacts than the reference case. This discourages their application in sustainable construction industry.